ENSURING TRANSPARENCY AND INFORMATION OPENNESS OF GENERAL SECONDARY EDUCATION IN KYIV - Lynova, Iryna; Pleshko, Tatiana (Educological discourse, 2020)
The article offers consideration of the results of the analysis of the State Service for Education Quality in Kyiv of the sites of educational institutions of communal, state and private forms of ownership of the city of Kyiv in relation to their availability and occupancy on 21 indicators: charter of educational institution; licenses for educational activities; structure and governing bodies of the educational institution; staff in accordance with the license conditions; educational programs implemented in the educational institution and the list of educational components provided by the relevant educational program; service area assigned to the educational institution by its founder (for preschool and general secondary education institutions); licensed volume and actual number of students; language (languages) of the educational process; availability of vacant positions, procedure and conditions of the competition for their replacement (in case of its holding); material and technical support of the educational institution (according to the license conditions); results of monitoring the quality of education; annual report on the activities of the educational institution; admission rules; conditions of accessibility of the educational institution for training of persons with special educational needs; tuition fees for private schools); list of additional educational and other services, their cost, procedure for provision and payment; rules of conduct for students; a plan of measures aimed at preventing and combating bullying in the educational institution; the procedure for submitting and reviewing (with confidentiality) applications for cases of bullying (harassment) in an educational institution, response and responsibility of persons in an educational institution involved in bullying (harassment). The authors of the article developed 518 sites of schools of various forms of ownership: state and communal forms of ownership - 437, private - 81. On average, according to 21 indicators, 56% of schools publish the necessary information on the websites of general secondary education institutions. The authors hope that the comments and suggestions set out in the conclusions to the article will help schools to systematize information about their lives and prospects.